Penguatan Legalitas BUMDes Bina Margaasih melalui Pendampingan Partisipatif Berbasis MBKM - Aditya, Tiara Putri (Community Empowerment : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
The institutional stagnation of BUMDes Bina Margaasih stems from the absence of key legal components, including the deed of establishment, statutes/bylaws (AD/ART), and other formal documents. This lack of legal foundation limits the BUMDes’ ability to access partnerships, funding, and public legitimacy. This community service initiative aimed to support the legal establishment of BUMDes through a participatory approach rooted in the Merdeka Belajar Kampus Merdeka (MBKM) program. Using the Participatory Action Research (PAR) method, the project fostered collaboration among village authorities, BUMDes administrators, village facilitators, academics, and students. The process involved identifying institutional needs, drafting legal documents such as village regulations (Perdes), bylaws (AD/ART), and a business plan, and completing the official registration through the Ministry of Law and Human Rights system. The results indicate that the participatory approach significantly enhanced the village’s institutional capacity, accelerated the legalization process, and produced regulation-compliant documents. The issuance of the BUMDes Bina Margaasih legal entity certificate by the Ministry of Law and Human Rights marked the success of the initiative. This legal status provides a critical foundation for achieving transparent, accountable, and sustainable village economic governance